2016
DOI: 10.1515/cclm-2015-1276
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of macrotroponin I with a high-sensitivity troponin I assay

Abstract: Background:Cardiac troponin is the preferred biomarker of myocardial injury. High-sensitivity troponin assays allow measurement of very low levels of troponin with excellent precision. After the introduction of a high-sensitivity troponin I assay the laboratory began to receive enquiries from clinicians about clinically discordant elevated troponin I results. This led to a systematic investigation and characterisation of the cause.Methods:Routine clinical samples were measured by the Architect High Sensitive T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 36 publications
(40 reference statements)
1
59
0
3
Order By: Relevance
“…False-positive hs-cTn results may also be attributed to the presence of complexes between antibodies and cTn, resulting in a delayed clearance of the macrocomplex from the circulation. Initially recognized by Plebani et al [73], the presence of macrotroponin I was identified in 5% of patients with elevated hs-cTn I values, when measured with the Abbott Architect assay; but given the biological characteristics of the interferent, the investigated assay may not be the only hs-cTn I assay affected by this problem [74]. A case of macrotroponin T has been also reported [75].…”
Section: Understanding the Impact Of Pre-analytical And Analytical Inmentioning
confidence: 99%
“…False-positive hs-cTn results may also be attributed to the presence of complexes between antibodies and cTn, resulting in a delayed clearance of the macrocomplex from the circulation. Initially recognized by Plebani et al [73], the presence of macrotroponin I was identified in 5% of patients with elevated hs-cTn I values, when measured with the Abbott Architect assay; but given the biological characteristics of the interferent, the investigated assay may not be the only hs-cTn I assay affected by this problem [74]. A case of macrotroponin T has been also reported [75].…”
Section: Understanding the Impact Of Pre-analytical And Analytical Inmentioning
confidence: 99%
“…It is well known that interferences from, for example troponin macro-aggregate [70,71] and heterophilic [72] or auto-antibodies [73], may produce aberrant results in troponin testing in individual samples. Finally, the EP28-A3c IFCC-CLSI document [66] recommends that all pre-analytical factors (including subjects preparation, sample collection and processing), the analytical method procedure (including lot-to-lot variation of materials and calibrators) and instrumentation must be carefully defined and used for testing the reference individuals in order to minimize the number of aberrant results.…”
Section: Statistical Considerationsmentioning
confidence: 99%
“…It appears that the autoantibodies are directed against cTnI but only when it is in the circulating cTnI-cTnC-cTnT (I-T-C) complex [29]. The prevalence of circulating antibodies to cTnI have been described as between 5% [30] and 12.5% [31]. This is much higher than seen in routine clinical practice and implies we are missing a substantial number of cases.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The general principles of PEG precipitation of macro-complexes can be applied to any smallish molecule bound to an immunoglobulin. There have been reports of macro-TSH being investigated with PEG precipitation [16,54] and also troponin [30,55]. However, the behaviour of any assay used in conjunction with PEG precipitation needs to be carefully validated before use.…”
Section: Polyethylene Glycol (Peg) Precipitationmentioning
confidence: 99%
See 1 more Smart Citation